Caracterização molecular de enterobactérias resistentes aos carbapenêmicos - Marques, Jaciane Baggiotto (2014)
Enterobacteriaceae resistant to carbapenems cause great impact on public health due to their different evolutionary mechanisms of resistance. The mechanism of resistance that recently has been reported in Enterobacteriaceae is due to production of carbapenemases. Carbapenemases are enzymes that act against carbapenems such as meropenem, ertapenem, and imipenem. The most frequently reported are the metallo-β-Lactamases and serin-carbapenemases, which are classified according to their molecular structure. The detection of such enzymes is a challenge faced in many clinical laboratories due to the delay in obtaining results and use of not very sensitive methods. The present study aimed to characterize genotypic and phenotypically clinical isolates of carbapenem-resistant Enterobateriaceae, during over seven months, isolated from inpatients at the University Hospital of Santa Maria. Results show that the modified Hodge (MHT) test is able to identify, in most cases, the strains producing any kind of resistance. Similarly, the search for genes - through PCR - was effective in identifying carbapenemase enzymes such as blaKPC, blaIMP e blaVIM. Therefore, none of these methods alone is enough for the detection of resistance mechanisms. Therefore, the combined use of the methods is needed to identify the resistance to carbapenems produced by enterobacteria to prevent its spread and promote the control of infections caused by these organisms.